Playing with America's Doll : A Cultural Analysis of the American Girl Collection - Zaslow, Emilie (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2017)
This critical account of the American Girl brand explores what its books and dolls communicate to girls about femininity, racial identity, ethnicity, and what it means to be an American. Emilie Zaslow begins by tracing the development of American Girl and situates the company's growth and popularity in a social history of girl power media culture. She then weaves analyses of the collection's narrative and material representations with qualitative research on mothers and girls. Examining the dolls with both a critical eye and a fan's curiosity, Zaslow raises questions about the values espoused by this iconic American brand.